2018
DOI: 10.1007/s00348-018-2655-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a canonical helicopter hub wake

Abstract: The current study investigates the long-age wake behind rotating helicopter hub models composed of geometrically simple, canonical bluff body shapes. The models consisted of a 4-arm rotor mounted on a shaft above a 2-arm (scissor) rotor with all the rotor arms having a rectangular cross-section. The relative phase between the 2-and 4-arm rotors was either 0° (in-phase) or 45° (out-of-phase). The rotors were oriented at zero angle-of-attack and rotated at 30 Hz. Their wakes were measured with particle-image-vel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…The projected area of the models varied with configuration and tilt angle producing ratios of solid blockage area to total area ranging from 3.4% (dual parallel at 0°tilt angle) to 9.6% (quad-plus at 30°tilt angle). This range of blockage is comparable to traditional helicopter hub water tunnel experiments with values above 8% [25,26], which those studies reported negligible impact from blockage on the results. Correcting the freestream speed for the solid blockage increases the Reynolds number and advance ratio for the 0.5 m/s condition by less than 7%.…”
Section: Laboratory Testingsupporting
confidence: 80%
“…The projected area of the models varied with configuration and tilt angle producing ratios of solid blockage area to total area ranging from 3.4% (dual parallel at 0°tilt angle) to 9.6% (quad-plus at 30°tilt angle). This range of blockage is comparable to traditional helicopter hub water tunnel experiments with values above 8% [25,26], which those studies reported negligible impact from blockage on the results. Correcting the freestream speed for the solid blockage increases the Reynolds number and advance ratio for the 0.5 m/s condition by less than 7%.…”
Section: Laboratory Testingsupporting
confidence: 80%